'Green incubation': avian offspring benefit from aromatic nest herbs through improved parental incubation behaviour. Issue 1880 (6th June 2018) - Gwinner, Helga; Capilla-Lasheras, Pablo; Cooper, Caren; Helm, Barbara
Abstract : Development of avian embryos requires thermal energy, usually from parents. Parents may, however, trade off catering for embryonic requirements against their own need to forage through intermittent incubation. This dynamically adjusted behaviour can be affected by properties of the nest. Here, we experimentally show a novel mechanism by which parents, through incorporation of aromatic herbs into nests, effectively modify their incubation behaviour to the benefit of their offspring. Our study species, the European starling, includes in its nest aromatic herbs which promote offspring fitness. We provided wild starlings with artificial nests including or excluding the typically selected fresh herbs and found strong support for our prediction of facilitated incubation. Herb effects were not explained by thermal changes of the nests per se, but by modified parental behaviours. Egg temperatures and nest attendance were higher in herb than herbless nests, egg temperatures dropped less frequently below critical thresholds and parents started their active day earlier. These effects were dynamic over time and particularly strong during early incubation. Incubation period was shorter in herb nests, and nestlings were heavier one week after hatching. Aromatic herbs hence influenced incubation in beneficial ways for offspring, possibly through pharmacological effects on incubating parents.